FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA CAKUPAN IMUNISASI MR (MEASLES RUBELLA) PADA BALITA - Wilda Wahyuni Siregar; Rina Purnama Nasution; Nita Triana Saragih; Diah Evawanna Anuhgerah (JURNAL KEBIDANAN KESTRA (JKK), 2021)
Measles and rubella is infectious diseases caused by measles virus and rubella transmitted through the respiratory tract. Measles and rubella highly contagious, and transmitted through splash sneezing or cough. Children who have never got measles and rubella immunization, or who have never had measles and rubella is the high risk of contracting the disiase.This study aims to know the factors related to the low coverage measles, rubella on toddler in the village of Simpang Tiga Pekan district Perbaungan district Serdang bedagai Year 2019. Research used in this study is deskritif quantitative by using the design of cross-sectional. Population in this study is around the mother that has a toddler 9 -59 months are in the village of Simpang Tiga Pekan. Sampling is done by techniques accidental sampling by the number of samles as much as 36 respondents. Research instruments by using the quetionnaire. Data were analyzed by univariate, bivariate with the chi-square test at level 95%, Î± = 5%. confidence. Analysis shows that there relationship knowledge mother by administering immunization MR (Measles, Rubella) with 95% (Î± = 0,05) p value = 0,000 confidence level, that there relationship attitude mother by administering immunization MR with 95% (Î± = 0,05) p value = 0,000 confidence level, that there relationship resources mother by administering immunization MR with 95% (Î± = 0,05) p value = 0,000 confidence level. Suuggested to mothers should always come at activities posyandu and do immunization regularly and active role in the activities of immunization and search for related information immunization in toddlers.